Improved thermal stability and flame resistance of flexible polyimide foams by vermiculite reinforcement. Issue 20 (10th February 2017) - Yan, Li; Fu, Liwei; Chen, Yajun; Tian, Huafeng; Xiang, Aimin; Rajulu, A. Varada
ABSTRACT: In this work, a series of flexible polyimide composite foams with dianhydride and isocyanate as the starting materials were prepared by pre‐dispersing vermiculite in isocyanate. The experimental results revealed that the cellular diameter of foams obviously decreased with the addition of vermiculite. The open cell content decreased with the increase of vermiculite, and foams containing vermiculite possessed higher apparent densities of about 10 kg/m 3 when compared with the neat polyimide foams. The compressive strength was dramatically enhanced by vermiculite incorporation, and reached maximum when the filler content was 2%, indicating dramatically reinforcing effect of vermiculite. With the addition of vermiculite, the thermal stability and flame resistance of polyimide foams were improved. The limiting oxygen index of polyimide foams showed an increase from 31 to 33.5% with increase of vermiculite from 0 to 8% and the peak heat release rate decreased, indicating high flame retardant properties. Vermiculites possess excellent heat insulation and high temperature stability. When conditioned at high temperature, the filler would block the heat transfer during the bulk foam. Therefore, it is feasible to further increase the mechanical and thermal properties of polyimide foams by vermiculite filling. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44828. Abstract :